A study on the trend toward financial statement analysis of Prudential Assurance Malaysia Berhad / Siti Zubaidah Abdullah - Abdullah, Siti Zubaidah (2011)
Prudential Assurance Malaysia Berhad (PAMB) is under Prudential PLC, United Kingdom and was established in Malaysia since 1924. The foundation why the researcher accomplishes this study is because the researcher wants to see the trend of Prudential’s financial statement over the past 5 years starting from 2004 to 2009. In view of the fact that PAMB is under international company, so the researcher want to study the trend of financial ratio of Prudential in 2008/2009 during global economic crisis and distinguish whether during world economic crisis in 2008/2009, is it the financial statement of PAMB was affected or not by the global economic crisis. In a way, the researcher will calculate the ratio analysis in order to know the uptrend or downtrend of company’s financial statement. The researcher will study the factor contribute to the trend of company’s financial performance and the researcher also want to recognize what is the best strategy the company can take in order to sustain their good uptrend or what they can do if the financial statement going downtrend.